2020
DOI: 10.1016/j.dsr2.2020.104812
|View full text |Cite
|
Sign up to set email alerts
|

Micronekton distribution as influenced by mesoscale eddies, Madagascar shelf and shallow seamounts in the south-western Indian Ocean: an acoustic approach

Abstract: An investigation of the vertical and horizontal distributions of micronekton, as influenced by mesoscale eddies, the Madagascar shelf and shallow seamounts, was undertaken using acoustic data collected during two research cruises at an unnamed pinnacle (summit depth ∼240 m) thereafter named "MAD-Ridge", and at La Pérouse seamount (∼60 m) in the south-western Indian Ocean. MAD-Ridge is located to the south of Madagascar, in an "eddy corridor", known both for its high mesoscale activity and high primary producti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
23
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 98 publications
1
23
0
Order By: Relevance
“…Local productivity at MAD-Ridge did not result from a Taylor column (Annasawmy et al, 2019c) since the latter may form transiently, under specific conditions of summit depth, water column stratification and current speeds (Owens & Hogg, 1980, Freeland, 1994, Mohn et al, 2009, Wagawa et al, 2012Bashmachnikov et al, 2013). concluded that while, Taylor columns may theoretically be formed over several seamounts of the Madagascar Ridge, the relatively strong currents associated with mesoscale eddies may prevent their formation or sweep away any incipient Taylor cap before settlement.…”
Section: Sampling Biases and Constraintsmentioning
confidence: 97%
See 4 more Smart Citations
“…Local productivity at MAD-Ridge did not result from a Taylor column (Annasawmy et al, 2019c) since the latter may form transiently, under specific conditions of summit depth, water column stratification and current speeds (Owens & Hogg, 1980, Freeland, 1994, Mohn et al, 2009, Wagawa et al, 2012Bashmachnikov et al, 2013). concluded that while, Taylor columns may theoretically be formed over several seamounts of the Madagascar Ridge, the relatively strong currents associated with mesoscale eddies may prevent their formation or sweep away any incipient Taylor cap before settlement.…”
Section: Sampling Biases and Constraintsmentioning
confidence: 97%
“…Eddies are well known in influencing local water properties, such as the trapping of anomalous water masses (Swart et al, 2010;Pollard & Read, 2015), or the advection of coastal waters with high phytoplankton biomass from the coast to open waters (Quartly & Srokosz, 2004;Tew-Kai & Marsac, 2009;Kolasinski et al, 2012). Coastally upwelled waters of high biological productivity over the southern Madagascar shelf (Ramanantsoa et al, 2018) may be trapped by mesoscale features that propagate over MAD-Ridge (Annasawmy et al, 2019c).…”
Section: Sampling Biases and Constraintsmentioning
confidence: 99%
See 3 more Smart Citations